Green's function method to the ground state properties of a two-component Bose-Einstein condensate: Бозе-эйнштейновская конденсация - Liang, Chen; Wei, Kong; Ye, B.J.; Wen, H.M.; Zhou, X.Y.; Han, R.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The elementary excitation spectrum of a two-component Bose–Einstein condensate is obtained by Green’sfunction method. It is found to have two branches. In the long-wave limit, the two branches of the excitation spectrum are reduced to one phonon excitation and one single-particle excitation. With the obtained excitation spectrum and the Green’s functions, the depletion of the condensate and the ground state energy have also been calculated in this paper.